2012
DOI: 10.3892/etm.2012.469
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism at the miR-502 binding site in the 3′ untranslated region of the SET8 gene is associated with the outcome of small-cell lung cancer

Abstract: microRNAs (miRNAs) bind to the 3' untranslated regions (UTRs) of messenger RNAs, where they interfere with translation of genes that regulate cell differentiation, apoptosis and tumourigenesis. The histone methyltransferase SET8 has been reported to methylate TP53 and regulate genomic stability. We analysed a single nucleotide polymorphism (rs16917496) within the miR-502 miRNA seed region at the 3' UTR of SET8 in small-cell lung cancer (SCLC) patients. The SET8 CC+CT genotype was identified to be independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
3
34
0
1
Order By: Relevance
“…The CC genotype was associated with longer survival time and a decreased risk of death in NSCLC patients (Xu et al, 2013a). Similarly, the CC+CT genotype was closely associated with longer survival of SCLC patients (Ding et al, 2012). SNP rs2239680 in the miR-335 binding site of the oncogene BIRC5 may alter the susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 93%
“…The CC genotype was associated with longer survival time and a decreased risk of death in NSCLC patients (Xu et al, 2013a). Similarly, the CC+CT genotype was closely associated with longer survival of SCLC patients (Ding et al, 2012). SNP rs2239680 in the miR-335 binding site of the oncogene BIRC5 may alter the susceptibility to lung cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the RNA-induced silencing complex (RISC) including GEMIN3 and GEMIN4 selects a single strand as the mature miRNA and guides the mature miRNAs to their target mRNA sites (10,13-16). miRNA-related single nucleotide polymorphisms (miR-SNPs), defined as SNPs in miRNA genes, miRNA binding site and miRNA processing machinery, are able to modulate miRNA and target gene expressions in order to influence cancer risk, treatment efficacy and patient prognosis (9,(17)(18)(19)(20).A miR-SNP of rs11077 located in the 3'UTR of the miRNA processing gene XPO5 has shown its association with the chemotherapeutic response in metastatic colon cancer as well as recurrence in resected non-small cell lung cancer (NSCLC) (9,19). In the present study, we evaluated the predictive power of this SNP on the overall survival of SCLC patients.…”
mentioning
confidence: 99%
“…SET8 has been shown to be correlated with a series of human tumors, such as hepatocellular cancer, breast cancer, ovarian cancer, and lung cancer (Song et al, 2009;Ding et al, 2012;Guo et al, 2012;Wang et al, 2012;Xu et al, 2013). However, no studies have demonstrated a correlation between SET8 and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%